The challenges that basic stage EFL students face in online listening comprehension from their teachers’ perspectives in Jordan - Yousef, Rawan (Technium Social Sciences Journal, 2023)
This study explored the challenges that Basic Stage EFL students encountered in online listening comprehension from their teachers’ perspectives during the Corona Virus pandemic. It included (161) EFL teachers from public schools in Jordan who were randomly selected from Marka Directorate of Education in Amman during the first semester of the academic year 2021/2022. A special questionnaire was developed for data collection. The results indicated that teachers regardless of their experience and gender confirmed a set of challenges that face EFL students in online listening comprehension. The results also revealed that the students’ domain of these challenges received the highest mean score. Based on the study’s results, the researcher proposed some recommendations to overcome online listening comprehension challenges.